Sequence-dependent inhibition of cGAS and TLR9 DNA sensing by 2′-O-methyl gapmer oligonucleotides. Issue 11 (31st May 2021) - Valentin, Roxane; Wong, Christophe; Alharbi, Arwaf S; Pradeloux, Solène; Morros, Makala P; Lennox, Kim A; Ellyard, Julia I; Garcin, Aurélie J; Ullah, Tomalika R; Kusuma, Gina D; Pépin, Geneviève; Li, Hong-Mei; et al.
Abstract: Oligonucleotide-based therapeutics have the capacity to engage with nucleic acid immune sensors to activate or block their response, but a detailed understanding of these immunomodulatory effects is currently lacking. We recently showed that 2′- O -methyl (2′OMe) gapmer antisense oligonucleotides (ASOs) exhibited sequence-dependent inhibition of sensing by the RNA sensor Toll-Like Receptor (TLR) 7. Here we discovered that 2′OMe ASOs can also display sequence-dependent inhibitory effects on two major sensors of DNA, namely cyclic GMP-AMP synthase (cGAS) and TLR9. Through a screen of 80 2′OMe ASOs and sequence mutants, we characterized key features within the 20-mer ASOs regulating cGAS and TLR9 inhibition, and identified a highly potent cGAS inhibitor. Importantly, we show that the features of ASOs inhibiting TLR9 differ from those inhibiting cGAS, with only a few sequences inhibiting both pathways. Together with our previous studies, our work reveals a complex pattern of immunomodulation where 95% of the ASOs tested inhibited at least one of TLR7, TLR9 or cGAS by ≥30%, which may confound interpretation of their in vivo functions. Our studies constitute the broadest analysis of the immunomodulatory effect of 2′OMe ASOs on nucleic acid sensing to date and will support refinement of their therapeutic development.